TED-Ed platform as a tool develop English teaching undergraduate students’ listening comprehension skiils - PEREIRA, Nayra Aparecida Costa (2024)
This paper presents a pedagogical proposal for English language teachers in higher education, based on the TED-Ed platform. The practice aims to use educational videos and demonstrates that the use of audiovisual resources can add to the teaching of listening comprehension skills in an additional language. The theoretical contributions that underpin listening skills and strategies are mainly based on the ideas and concepts of the authors Morley (1991), Harmer (1998), Field (2002), Brown (2007-2006), Nunan (2006), David (2008), Rost (2011), and others. In this respect, the proposal is aimed at intermediate level and undergraduate teachers, considering that the use of TED-Ed videos can contribute to the process of teaching listening. This research also offers a more comprehensive understanding of the use of TED-Ed as pedagogical support for teaching. Finally, this research is a useful contribution to the analyses that highlight language teaching through the use of audiovisual and technological resources to improve listening skills.